Guidance services delivery system needs assessment and program development - Guzman, Luzviminda S.
Using the descriptive survey research methodology, this study assessed the guidance services delivery system of the Cagayan State University. It was done in two stages: first, in the first semester of SY 1990-1991 among 482 respondents, and second, in the first semester of SY 1991-1992 with 592 respondents. Data gathering was undertaken using the Guidance Service Inventory (GSI), the Student Needs Inventory (SNI), interviews, documentary analysis, and actual observation. The first five concerns clustered around financial, counseling, career, academic, and testing. On the basis of the results of the study a revitalized guidance program was formulated and recommended as a model for the guidance services in the different units of the Cagayan State University.